2021
DOI: 10.21037/apm-21-464
|View full text |Cite
|
Sign up to set email alerts
|

Venous thromboembolism risk factors and prophylaxis of elderly intensive care unit patients in a Chinese general hospital

Abstract: deaths occurring during hospitalization, especially in elderly patients. Approximately 18% to 65% of VTE-associated mortality has been reported as being preventable (2). Multimorbidity, which is defined as the co-occurrence of 2 or more chronic comorbidities is the common characteristic in the majority of elderly patients. We present the following article in accordance with the STARD reporting checklist

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…The Caprini risk assessment model can effectively predict the risk of VTE occurrence in patients admitted to the internal medicine intensive care unit and cerebrovascular disease patients. 23 25 …”
Section: Discussionmentioning
confidence: 99%
“…The Caprini risk assessment model can effectively predict the risk of VTE occurrence in patients admitted to the internal medicine intensive care unit and cerebrovascular disease patients. 23 25 …”
Section: Discussionmentioning
confidence: 99%
“…Wang et al showed that hypertension, cancer or systemic cancer treatments, diabetes, coronary heart disease, heart failure, respiratory failure, acute myocardial infarction, and ischemic stroke were associated with the risk of VTE in older adult ICU patients [ 28 ]. Chen et al [ 12 ] indicated that gender (male), bedridden for > 72 h, pneumonia, history of DVT, diabetes, coronary heart disease, glucocorticoids, PaO 2 , mechanical ventilation, CRRT, hemoglobin level, PT, INR, and D-dimer level were risk factors for VTE in critically ill older adult patients. The discrepancies in risk factors among studies might be due to the exact ICU population, local clinical practice, variables being examined, and different definitions used.…”
Section: Discussionmentioning
confidence: 99%
“…Length of stay in the ICU and older age are two important risk factors for DVT [ 7 , 8 ], while further research needs to be conducted to clarify the exact risk factors for DVT in critically ill older adult patients. A recent study showed that the risk factors for venous thromboembolism in critically ill older adult patients were sex (male), bedridden for > 72 h, pneumonia, history of DVT, diabetes, coronary heart disease, glucocorticoids, PaO 2 level, mechanical ventilation, continuous renal replacement therapy (CRRT), prothrombin time (PT), international normalized ratio (INR), and D-dimer level [ 12 ], while it was a retrospective study with a risk of bias. Therefore, prospective cohort studies are necessary to identify the risk factors of DVT in critically ill older adult patients.…”
Section: Introductionmentioning
confidence: 99%
“…Six trials enrolled 10,112 critically ill medical and surgical patients to assess individual VTE risk by the CRS (Table S16, Supplemental Digital Content 1, http://links.lww.com/SLA/ E469). [76][77][78][79][80][81] The incidence of VTE varied between 3.1% and 8.9% while symptomatic events were detected in 3.1% to 7.9% of cases. The Caprini score ranged from 0 to 21.…”
Section: Critically Ill Patientsmentioning
confidence: 99%